Revisiting the legal status of Sabah and Sarawak in Malaysia - A Rahman Tang Abdullah (Journal of the Malaysian Branch of the Royal Asiatic Society, 2024)
The legal status of Sabah and Sarawak in the Malaysia Agreement of 1963 became a contentious issue for the Malaysian public because of claims that Sabah and Sarawak entered the Federation of Malaysia as equal partners with the whole of Peninsular Malaysia, rather than as states within the federation. A further claim is that a constitutional amendment in 1976 downgraded the status of Sabah and Sarawak to the same level as the 11 states in the Malay Peninsula, an argument found in propaganda issued in connection with the Sarawak State Election in 2016 and the Malaysian general Election in 2018. This paper refutes these claims, showing that under the Malaysia Agreement Sabah and Sarawak are simply two states within the federation, and that the constitutional amendment of 1976 did not change their legal status.